Magma‐Mush Interactions in the Lower Oceanic Crust: Insights From Atlantis Bank Layered Series (Southwest Indian Ridge). Issue 9 (12th September 2021) - Boulanger, M.; France, L.; Ferrando, C.; Ildefonse, B.; Ghosh, B.; Sanfilippo, A.; Liu, C.‐Z.; Morishita, T.; Koepke, J.; Bruguier, O.
Abstract: Magma migration and differentiation processes are key to understanding the development and evolution of oceanic magma reservoirs. To provide new quantitative geochemical constraints on these processes, we applied a high‐resolution approach to study an interlayered section of the lower oceanic crust sampled at Atlantis Bank, on the (ultra)slow‐spreading Southwest Indian Ridge. The section is characterized by sharp grain‐size layering between fine‐ and coarse‐grained olivine gabbros that is representative of other layered structures described at the Atlantis Bank oceanic core complex. The textures and fabrics of the layers and the nature of their contacts indicate formation by intrusion of a magma (i.e., crystal‐bearing) into an almost solidified coarse‐grained mush. Petrographic observations and in situ incompatible trace element signatures indicate that the fine‐ and coarse‐grained layers record reactive porous migration of melts. Widespread reactive porous flow occurred prior to intrusion within the coarse‐grained gabbro, producing mineral compositions enriched in incompatible elements. The intrusive fine‐grained lithology records a late stage event of localized reactive melt percolation in cm‐scale structures, which lead to strong light rare earth elements depletion relative to heavy rare earth elements. In addition, we highlight the occurrence of interactions at the contacts between layers and partial modification in compositions of the intruded lithology. This layered section likely represents a contact between two larger magma bodies emplaced within the lower crust during accretion, where the type of melt migration (intrusion or porous flow) and the modalities of melt percolation (widespread or localized) strongly govern the composition of the crustal lithologies. Plain Language Summary: We present the study of a 1m35 borehole section of oceanic crust exhumed at Atlantis Bank on the Southwest Indian Ridge. This section presents characteristic layering defined by successive fine‐ and coarse‐grained olivine gabbro layers, which recorded the conditions and modalities of magma emplacement and evolution during oceanic crust accretion. We conducted a high‐resolution study of samples collected continuously along the section, including a description of the petrography, analysis of microstructures, and geochemistry of both rocks and minerals. This high‐resolution approach allowed us to reconstruct the intricate formation steps of the section, which involves the two main melt migrations processes at depth: an intrusion, represented by the fine‐grained layers, and porous melt flow, which occurs at all steps of formation of the lithologies. The latter process strongly impacted the textures and composition of the lithologies. These compositions provide information on the modalities of the porous melt migration, which can be pervasive or focused in discrete structures. The geometry of the layer contacts together with the emplacement model suggests that this layering likely represents an irregular contact between two larger intrusions or magma reservoirs emplaced within the oceanic crust. Key Points: At slow‐spreading ridges, igneous layering in the lower crust records intrusive events of crystal‐bearing magmas At lower crustal levels, melt migration proceeds by intrusion and reactive porous flow Melt migration modes strongly influence the chemical compositions of melts, crystal matrices, and crustal lithologies